Mycobacterium tuberculosis-Specific CD4 T Cells Expressing Transcription Factors T-Bet or RORγT Associate with Bacterial Control in Granulomas - Nicole L. Grant; Kristen Kelly; Pauline Maiello; Helena Abbott; Shelby O’Connor; Philana Ling Lin; Charles A. Scanga; JoAnne L. Flynn (mBio, 2023)
ABSTRACT Despite the extensive research on CD4 T cells within the context of Mycobacterium tuberculosis (Mtb) infections, few studies have focused on identifying and investigating the profile of Mtb-specific T cells within lung granulomas. To facilitate the identification of Mtb-specific CD4 T cells, we identified immunodominant epitopes for two Mtb proteins, namely, Rv1196 and Rv0125, using a Mauritian cynomolgus macaque model of Mtb infection, thereby providing data for the synthesis of MHC class II tetramers. Using tetramers, we identified Mtb-specific cells within different immune compartments, postinfection. We found that granulomas were enriched sites for Mtb-specific cells and that tetramer+ cells had increased frequencies of the activation marker CD69 as well as the transcription factors T-bet and RORγT, compared to tetramer negative cells within the same sample. Our data revealed that while the frequency of Rv1196 tetramer+ cells was positively correlated with the granuloma bacterial burden, the frequency of RORγT or T-bet within tetramer+ cells was inversely correlated with the granuloma bacterial burden, thereby highlighting the importance of having activated, polarized, Mtb-specific cells for the control of Mtb in lung granulomas. IMPORTANCE Tuberculosis, caused by the bacterial pathogen Mycobacterium tuberculosis, kills 1.5 million people each year, despite the existence of effective drugs and a vaccine that is given to infants in most countries. Clearly, we need better vaccines against this disease. However, our understanding of the immune responses that are necessary to prevent tuberculosis is incomplete. This study seeks to understand the functions of T cells that are specific for M. tuberculosis at the site of the disease in the lungs. For this, we developed specialized tools called MHC class II tetramers to identify those T cells that can recognize M. tuberculosis and applied the tools to the study of this infection in nonhuman primate models that mimic human tuberculosis. We demonstrate that M. tuberculosis-specific T cells in lung lesions are associated with control of the bacteria only when those T cells are expressing certain functions, thereby highlighting the importance of combining the identification of specific T cells with functional analyses. Thus, we surmise that these functions of specific T cells are critical to the control of infection and should be considered as a part of the development of vaccines against tuberculosis.